Sterile protection against P. vivax malaria by repeated blood stage infection in the Aotus monkey model - Obaldía, Nicanor (2024)
The malaria parasite Plasmodium vivax remains a major global public health challenge, and no vaccine is approved for use in humans. Here, we assessed whether P. vivax strain-transcendent immunity can be achieved by repeated infection in Aotus monkeys. Sterile immunity was achieved after two homologous infections, whereas subsequent heterologous challenge provided only partial protection. IgG levels based on P. vivax lysate ELISA and protein microarray increased with repeated infections and correlated with the level of homologous protection. Parasite transcriptional profiles provided no evidence of major antigenic switching upon homologous or heterologous challenge. However, we observed significant sequence diversity and transcriptional differences in the P. vivax core gene repertoire between the two strains used in the study, suggesting that partial protection upon heterologous challenge is due to molecular differences between strains rather than immune evasion by antigenic switching. Our study demonstrates that sterile immunity against P. vivax can be achieved by repeated homologous blood stage infection in Aotus monkeys, thus providing a benchmark to test the efficacy of candidate blood stage P. vivax malaria vaccines.